Evaluation Follicular Fluid Cytokines in Patients with Risk Factor for Development of Ovarian Hyper Stimulation Syndrome (Medico Legal Update, 2021)
Aim of Study: Study the level of IL17 and IL23 in the follicular fluid and their relation with hyper stimulationsyndrome.Materials/Method: Eighty five who include (85 subject divided into 2 groups, control group whom includedinfertile female with male factor infertility (55) and case group whom infertility due to poly cystic ovariansyndrome (30) attended IVF centre.Samples collected were follicular fluid, the follicular fluid has been collected in Eppendorf tube then storedat -20c to be used for ELISA test to determine concentration of IL 23 and IL 17 in follicular fluid. The resultswere analyzed using the IBM SPSS analytic software.Results: the mean of interleukin (IL17) 96.11, Standard deviation 78.46 in the patients group. While themean of interleukin (IL 17) for control 6.15, Standard deviation 14.33. There was a significant differencebetween polycystic and male factor infertility. P value < 0.005 both of them groups Poly cystic and malefactor.Conclusions: High concentration of follicular fluid IL -17 is positively associated with e disease of polycystic ovary (POCS).